Reconstruction of pelvic ring, using the metal polymer еndoprosthesis after radical internal resection of pelvis - А. G. Diedkov; V. Yu. Коstiuk (Клінічна хірургія)
Objective. Investigation of the treatment results and quality of life in the patients, suffering pelvic bones tumors after radical surgical interventions.